A systematic review of improved positions and supporting devices for premature infants in the NICU. Issue 3 (March 2023) - Yang, Liu; Fu, Hua; Zhang, Lingping
Abstract: Background: In the neonatal intensive care unit, nurses often place premature infants in the supine, prone, and lateral positions. However, these positions do not always meet all the physiological needs of premature infants. Thus, many improved positions and various position-supporting devices have been studied to provide infants with a development-friendly and comfortable environment. Aim: We aimed to help nurses recognize and understand the various improved positions and devices, and to provide nurses with more options in addressing the needs of preterm infants. Study design: We searched PubMed, Web of Science, and EMBASE from 2012 to 2022 for studies on position management of preterm infants, and screened the search results according to inclusion and exclusion criteria. Then we extracted data and evaluated the quality of the included studies. Finally, we conducted a qualitative summary of the results. Results: Twenty-one articles were included in this review. Fourteen were studies about improved positions, including hammock position, facilitated tucking position, ROP position, reverse kangaroo mother care position (R-KMC), and supported diagonal flexion position (SDF). Seven were studies on positioning devices, four on cranial deformity prevention, and three on reformative swaddling. They have a positive impact on sleep and flexion maintenance, in addition, they can prevent head deformity and reduce the pain of premature infants. Conclusion: The position management of premature infants is diversified. Instead of sticking to a single position placement, nurses should adjust the position according to the unique physiological conditions of infants to reduce sequelae and promote their recovery and growth during long-term hospitalization. There should be more studies on position management with large sample sizes in the future.